Case 3779: Petalodus Owen, 1841 (Chondrichthyes, Petalodontiformes, Petalodontidae): proposed conservation of usage by designation of a neotype for its type species Petalodus hastingsii Owen, 1841. - Carpenter, Kenneth; Itano, Wayne (Bulletin of Zoological Nomenclature, 2018)
The purpose of this application, under Article 75.6 of the Code, is to confirm the availability and to maintain the usage of the genus Petalodus Owen, 1840, which is threatened by the identity of the type specimen of its type species Petalodus hastingsii Owen, 1840. The description and figure of the specimen by Owen (1840) do not match the actual specimen, nor does it resemble the subtriangular crowns traditionally referred to the form taxon Petalodus described and illustrated by Agassiz (1838: 108–109, pl. 19, figs. 11–13) as Chomatodus (subsequently Petalodus acuminatus by Agassiz, 1843: 159, 174, nota). Additional, more complete, specimens from the same bed and locality as Owen’s specimen were described and illustrated by Arthur Woodward (1889) as Petalodus acuminatus. The crowns of these teeth are labial-lingually compressed, vertically short, broad-based, subtriangular, and convex labially and concave lingually. In the subsequent 170 years, teeth identified and published as Petalodus have referred to the subtriangular teeth as described by Agassiz and Woodward, and not to the rectangular lamelliform tooth described by Owen. The Commission is therefore asked to exercise its plenary power to set aside the misleading and inadequate holotype, NHMUK PV P613, and designate as neotype specimen NHMUK PV P75414, a more complete tooth that shows all the characteristic features of Petalodus.
Keywords: Nomenclature; taxonomy; Carboniferous; Chondrichthyes; Petalodontidae; Petalodus; neotype; England